Is evoking fear effective? Exploratory findings from a randomised experiment on the impacts of health warning labels on sugar-sweetened beverages - Shelly Malik; Zoe Ong (Cambridge University Press, 2024)
Abstract Objective: Health warning labels (HWL) have been suggested to be effective in reducing consumption of sugar-sweetened beverages (SSB). Yet, the efficacy and acceptability of SSB HWL of different formats (textual/pictorial) and severity remain unclear. This exploratory study aims to examine the extent and mechanism through which HWL of different formats and severity may affect responses towards the HWL and SSB consumption. Design: Randomised online experiment. Participants were exposed to images of a hypothetical SSB bearing a HWL of one of three conditions: text-only HWL, moderately severe pictorial HWL and highly severe pictorial HWL. They then responded to theory-based affective, cognitive and behavioural measures. Setting: Singapore Participants: One hundred and twenty-seven young adult consumers from a public university Results: Direct effects were found for fear, avoidance, reactance and acceptability of the HWL, but not attitude, intention or motivation to consume less SSB. Pictorial (moderately severe and highly severe) HWL were associated with greater fear, avoidance, and reactance, and lower acceptability than text-only HWL. There was weak evidence that highly severe pictorial HWL resulted in greater reactance than moderately severe pictorial HWL. Fear mediated the effect of HWL of different severity levels on avoidance, reactance, intention and motivation, but not for attitude or acceptability. Conclusions: Exploratory findings indicate that although pictorial HWL were less acceptable, they may still be effective in influencing intention and motivation to reduce SSB consumption through the psychological mechanism of fear. Hence, graphic HWL should not be dismissed too quickly when considering strategies for reducing SSB consumption.